2021
DOI: 10.5114/wiitm.2021.105724
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial comparing the clinical outcomes of 3D versus 2D laparoscopic hysterectomy.

Abstract: Introduction:There have been a few clinical studies on the use of three-dimensional (3D) laparoscopy with different results. Aim: To compare the surgical outcomes of 3D versus two-dimensional (2D) laparoscopic hysterectomy for benign or premalignant gynecologic diseases. Material and methods: In this double-blind trial, 68 patients were randomly assigned to either the 3D or 2D groups at a 1 : 1 ratio. The only difference between the two groups was the laparoscopic vision system used. The primary outcome was op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Additionally, anesthesia can affect the body's temperature regulation, leading to an increase in body temperature. Infections are also a significant cause of postoperative fever 13,14 . In this study postoperative fever was observed in 5(6.40%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, anesthesia can affect the body's temperature regulation, leading to an increase in body temperature. Infections are also a significant cause of postoperative fever 13,14 . In this study postoperative fever was observed in 5(6.40%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…These drawbacks lie in the loss of depth perception when using a 2D endoscope, an unstable video camera when it is held manually, limited dexterity, counterintuitive and limited movement of LAP surgical instruments (due to the enforced fixation by the trocars and no deflection at the tip), the fulcrum effect, and very poor ergonomics for the surgeon and their assistants over extensive operation time [44,45]. Innovation in endoscopic systems such as high-resolution 3D cameras enabling better exposure and anatomical mapping of the operating space has recently further improved surgical performance during LAP [46][47][48]. Surgeons can now navigate anatomical structures with greater clarity, leading to improved outcomes and reduced operation times.…”
Section: Equivalence Of Ras and Lap In Technology Adoption Challenges...mentioning
confidence: 99%
“…[ 9 ] As early laparoscopic techniques relied on conventional two-dimensional (2D) imaging with limited depth perception, surgeons have to acquire different psychomotor skills as well as visuospatial competencies to work in a 3D abdominal space reflected in 2D images. [ 1 9 10 11 ] Attempts to address these concerns and to overcome the major drawback in the traditional 2D imaging system led to the development of 3D laparoscopy. [ 1 10 ]…”
mentioning
confidence: 99%
“…[ 1 9 10 11 ] Attempts to address these concerns and to overcome the major drawback in the traditional 2D imaging system led to the development of 3D laparoscopy. [ 1 10 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation